2011
DOI: 10.1115/1.4004083
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Near-Field Entrainment of Moderately Overpressured Jets

Abstract: Particle image velocimetry (PIV) experiments have been conducted to study the velocity flow fields in the developing flow region of high-speed jets. These velocity distributions were examined to determine the entrained mass flow over a range of geometric and flow conditions, including overpressured cases up to an overpressure ratio of 2.83. In the region near the jet exit, all measured flows exhibited the same entrainment up until the location of the first shock when overpressured. Beyond this location, the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…At steady state, K = 2.6, M = 1, and Re = 467,000. Steady state data is from Solovitz et al [], acquired at K = 2.55 ± 0.1.…”
Section: Resultsmentioning
confidence: 44%
See 3 more Smart Citations
“…At steady state, K = 2.6, M = 1, and Re = 467,000. Steady state data is from Solovitz et al [], acquired at K = 2.55 ± 0.1.…”
Section: Resultsmentioning
confidence: 44%
“…At the laboratory conditions, the speed of sound c = 343 m/s. In addition, Figure displays the steady state profile for a jet at similar conditions, as acquired by Solovitz et al []. Note that no data are shown closer than two diameters from the pipe due to illumination issues near the base plate wall.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the flow of the eruption column near the vent may deviate substantially from a self‐similar jet/plume (e.g., Carazzo et al, ; Suzuki & Koyaguchi, ). Recent experimental studies have indicated that the efficiency of entrainment varies with height even for idealized jets/plumes such as single‐phase gas jets (e.g., Solovitz et al, ). Therefore, the limitations of the entrainment hypothesis need to be assessed.…”
Section: Introductionmentioning
confidence: 99%